Chrysin ameliorates cerebral ischemia/reperfusion (I/R) injury in rats by regulating the PI3K/Akt/mTOR pathway. (October 2019) - Li, Teng-Fei; Ma, Ji; Han, Xin-Wei; Jia, Yong-Xu; Yuan, Hui-Fei; Shui, Shao-Feng; Guo, Dong; Yan, Lei
Abstract: In this study, the effects of chrysin on cerebral ischemia by establishing middle cerebral artery occlusion (MCAO) in rat were investigated. In vivo experiments, the rats were orally administrated with clopidogrel or chrysin once daily for 7 days before the experimental of ischemia and the rats were divided into 5 groups: the sham group, the I/R group, I/R + clopidogrel group, I/R + chrysin (10 mg/kg), I/R + chrysin (20 mg/kg) group. Chrysin significantly ameliorated the I/R rats, evaluated by TTC staining, determination of brain wet to dry weight ratio and neurological deficits. Moreover, in serum and brain tissues of the I/R rats, chrysin also could effectively suppress the release of inflammatory cytokines, including levels of interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). In addition, chrysin could improve the SOD activity in the I/R rats. Mechanically, chrysin could activate the PI3K/Akt/mTOR pathway, inhibited inflammation and apoptosis. In oxygen-glucose deprivation and recovery (OGD/R)-induced SH-SY5Y cells in vitro . Chrysin markedly decreased the levels of TNF-α, IL-6 and IL-1β in supernatant of OGD/R-induced SH-SY5Y cells via activating PI3K/Akt/mTOR pathway. In conclusion, our study demonstrated that chrysin might be a potential therapeutic agent for cerebral ischemia. Highlights: Chrysin alleviates ischemia/reperfusion injury. Chrysin has strong anti-inflammatory and anti-apoptosis effect. Chrysin inhibits the PI3K/Akt/mTOR pathway.